Genealogy of Discourse in Agitative Messages from Agus Harimurti Yudhoyono's Press Conference Regarding the Issue of the Democratic Party Coup - Probo Dwi Sasongko, Yohanes (e-Journal of Linguistics, 2021)
Language has power and knowledge. Through language, interpersonal communication between humans can bring about changes in attitudes, perceptions and behavior of society. The important role in human interpersonal communication, especially in political communication, leads to findings that are expected to produce thoughts independently. In the discourse text of Agus Harimurti Yudhoyono (AHY) 's speech, during a press conference regarding the news about the coup issue within the Democratic Party. Text discourse that is read articulatively in public, with a target orientation of the speech delivery process aimed at the government reaches its own anti-climax. By using Faucault genealogy discourse methodology, AHY's speech text discourse study presents its own understanding in society. The data found by reviewing the use of diction in text sentences, use of references, substitutions, ellipsis and conjunctive. brings a number of accurate information and explanations as a whole, that the contribution of language and the presence of communication in responding to and seeing the overall context of the news becomes a separate medium for studying the dynamic contexts of language in an integrated manner.